Comparative Analysis of the Oxygen Supply and Viability of Human Osteoblasts in Three-Dimensional Titanium Scaffolds Produced by Laser-Beam or Electron-Beam Melting - Jonitz-Heincke, Anika (Materials (Basel), 2013)
Synthetic materials for bone replacement must ensure a sufficient mechanical stability and an adequate cell proliferation within the structures. Hereby, titanium materials are suitable for producing patient-individual porous bone scaffolds by using generative techniques. In this in vitro study, the viability of human osteoblasts was investigated in porous 3D Ti6Al4V scaffolds, which were produced by electron-beam (EBM) or laser-beam melting (LBM). For each examination, two cylindrical scaffolds (30 mm × 10 mm in size, 700 µm × 700 µm macropores) were placed on each other and seeded with cells. The oxygen consumption and the acidification in the center of the structures were investigated by means of microsensors. Additionally, the synthesis of pro-collagen type 1 was analyzed. On the LBM titanium scaffolds, vital bone cells were detected in the center and in the periphery after 8 days of cultivation. In the EBM titanium constructs, however, vital cells were only visible in the center. During the cultivation period, the cells increasingly produced procollagen type 1 in both scaffolds. In comparison to the periphery, the oxygen content in the center of the scaffolds slightly decreased. Furthermore, a slight acidification of the medium was detectable. Compared to LBM, the EBM titanium scaffolds showed a less favorable behavior with regard to cell seeding.